2018
DOI: 10.1155/2018/9098215
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Expression Is Associated with the Poor Prognosis in Patients with Locally Advanced Esophageal Squamous Cell Carcinoma Receiving Preoperative Chemoradiotherapy

Abstract: Background The osteopontin has been involved in therapeutic resistance in a variety of cancers. But, the significance of osteopontin expression on the prognosis of patients with locally advanced esophageal squamous cell carcinoma (ESCC) receiving chemoradiotherapy is unclear. Methods In 80 patients with locally advanced ESCC receiving preoperative chemoradiotherapy between 1999 and 2012, osteopontin expression was evaluated by immunohistochemistry and correlated with treatment outcome. The functional role of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Further analysis demonstrated that differentially expressed immune signatures in ESCC might be crucial to tumorigenesis and development by activating T cell and NF-kappa B signaling pathways [ 36 ]. Recently, SPP1 expression was reported to be associated with poor prognosis in locally advanced ESCC patients receiving preoperative chemoradiotherapy [ 37 ]. A meta-analysis involving 811 patients showed that overexpression of SPP1 might be a promising independent prognostic risk factor for ESCC patients in China and Japan [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis demonstrated that differentially expressed immune signatures in ESCC might be crucial to tumorigenesis and development by activating T cell and NF-kappa B signaling pathways [ 36 ]. Recently, SPP1 expression was reported to be associated with poor prognosis in locally advanced ESCC patients receiving preoperative chemoradiotherapy [ 37 ]. A meta-analysis involving 811 patients showed that overexpression of SPP1 might be a promising independent prognostic risk factor for ESCC patients in China and Japan [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical staging was determined according to image examinations including a computed tomography (CT) scan of the abdomen and chest, endoscopic ultrasound (EUS), and/or positron emission tomography (PET) scan. The protocol of neoadjuvant chemoradiotherapy followed by esophagectomy was previously described [14,27]. Overall survival (OS) was computed from diagnosis date until the death date or the last follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the treatment outcome of the patients with ESCC receiving esophagectomy alone remains poor [2, 4, 5]. While the efficacy of preoperative therapy is relatively clear, the effect of postoperative adjuvant therapy remains controversial [14, 15]. Several studies of post-operative adjuvant therapy have been performed in an attempt to improve upon the survival rate achieved with esophagectomy alone, but the results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%